Islamic Law Analysis of Nazir Roles in Managing Waqf Assets in Indonesia - Deonard Faishal Ghazy; Khoiruddin Khoiruddin; Herlina Kurniati (UIN Siber Syekh Nurjati Cirebon, 2025)
Waqf governance in Indonesia has a strong legal basis, yet many waqf assets remain underutilized because nazir performance often stays administrative rather than welfare-oriented. This study examines the normative–empirical gap between Islamic legal expectations for nazir and actual waqf management practices in Lampung Province. The study applies a qualitative juridical-empirical approach, integrating Islamic law and Indonesia’s waqf legal framework with field evidence. Data were gathered through in-depth interviews with key stakeholders (BWI Lampung, the Regional Office of the Ministry of Religious Affairs, and a nazir from PW Muhammadiyah Lampung) and supported by institutional documents. Nazir practice generally fulfills basic custodial functions and conventional utilization (religious and educational purposes) but remains conservative, with limited productive development. Persistent weaknesses appear in incomplete certification, fragmented documentation, weak reporting routines, and the largely formal use of SIWAK, which constrain transparency, accountability, and legal certainty. These patterns indicate that compliance is often minimal-formal and does not yet reflect Islamic governance values emphasizing amānah, mas’ūliyyah, and benefit maximization (maqāṣid al-waqf). Strengthening nazir capacity, reporting standards, and governance supervision is essential to unlock waqf’s socio-economic potential.Keywords: waqf governance; nazir; Islamic law; SIWAK; Lampung Province